Effect of Supplementation of Bypass Fat and Mineral Mixture on Uterine Involution and Fertility in Gir Cows - Sahoo, Bhubaneswar; Panchal, Mahesh T; Patel, Dignesh K; Patel, Jagadish A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was carried out on 18 advanced pregnant Gir cows, under two treatment (Group I, II) and control (Group III) groups, 6 cows in each. The cows under Group III were maintained as per routine farm feeding schedule, while cows under Group I and II were supplemented with mineral mixture containing rumen protected methionine and lysine @ 50 g/day/head. Additionally, animals in group I were supplemented with bypass fat @ at least 100 g/d/h during 30 days prepartum till 60 days postpartum. The postpartum reproductive events were monitored by USG (5-10 MHz linear array transducer). The mean cervical diameter and wall thickness in cows under control Group III were the highest on all days postpartum as compared to nutrient supplemented groups I & II. The values on day 7 were highest in all three groups and decreased gradually (p<0.01) on days 14 and 28/42 postpartum. The mean diameter and wall thickness of gravid uterine horn were not influenced by the nutrient supplementation in cows, and the values in all groups decreased gradually (p<0.01) from day 7 to 14 till day 28 postpartum, which thereafter did not vary much. The mean period of uterine involution and days for first estrus postpartum in treated Group I and II were significantly (p<0.05) lower than control Group III, with inverse finding on mean service period and conception rate (83.33, 33.33 and 16.66% in Gr I, II, III, resp) by day 120 postpartum. The bypass fat and mineral mixture supplementation had positive effects on uterine involution, early onset of postpartum estrus, better conception rate and reduced service period.